COMPARATIVE ANALYSIS OF THE LEXICON IN THE SECOND CHAPTER OF BULGHATIL MUSHTAQ AND TARJUMAN TURKI - Ganiyeva Barchinoy (Journals Park Publishing, 2025)
This paper presents a comparative linguistic analysis of the second chapters of two Mamluk-Kipchak manuscripts: Bulghatil Mushtaq (hereafter BM) by Jamal ad-Din at-Turki and Tarjumon Turkiy (hereafter TT). Both manuscripts, compiled in the 14th–15th centuries during the Mamluk era, reflect the widespread use and prestige of the Kipchak language in the military, administrative, and cultural contexts of Egypt and Greater Syria. This study focuses on the lexical classification of words in the Second chapter of both manuscripts including words related to natural geography, plant life, and urban terminology, revealing both structural parallels and distinctive stylistic features. The analysis shows that while the manuscripts share core vocabulary, their approaches to semantic elaboration, translation strategy, and terminological precision differ significantly. The research highlights how TT adopts a more didactic, explanatory style, while BM favors concise, dictionary-like definitions.
Keywords: Mamluk-Kipchak, Bulghatil Mushtaq, Tarjuman Turki, lexical analysis, Turkic philology, historical linguistics, Kipchak language, comparative study.